(untitled) (International Journal of Engineering and Computer Science, 2017)
Ad hoc network is a self configurable network where the mobile nodes act as routers and connected using wireless links. An ad hoc routing protocol is a standard that controls the movement of nodes. The primary goal of an ad hoc routing protocol is establishment of correct and efficient route between a pair of nodes; so that message may be delivered in time. This paper presents various types of ad hoc routing protocols along with their characteristics and functionalities